Blood Calcium Level and Its Correlation with Calcium Daily Intake, Calcium Supplementation & Clinical Symptoms in Women with Premenstrual Syndrome - Hidayat, Meilinah; Wardani, Komang RP; Purba, Bertha M; Apreza, Rendhy T (Journal of Medicine and Health, 2017)
Premenstrual syndrome (PMS) is complex of symptoms that occur during the luteal phase of the menstrual cycle. This study aimed to observe blood calcium levels differences between the patient and not the PMS, list the average intake of calcium / day among subjects, statistically analyze the relationship between calcium intake and blood calcium levels, and examine the effect of calcium supplementation on blood calcium levels and symptoms of PMS. We examined blood levels of calcium, analytical survey method using a cross-sectional study, experimental methods and PMS symptom questionnaires. The results showed that in the group of subjects SPM average blood calcium level, and the mean intake of calcium / day were lower than in non-PMS and showed a fairly correlation between the intake of calcium per day with blood calcium levels in SPM subjects. There is a significant relationship between increased calcium blood calcium levels and symptoms of PMS. The conclusions: 1. there are differences in blood calcium levels and 2. intake of calcium per day between patients with PMS and not PMS, 3. Calcium intake is significantly associated with calcium level in the PMS and 4. calcium supplementation affects blood calcium levels and reduce symptoms of PMS.Keywords : average calcium intake, blood calcium, calcium supplementation, Premenstrual Syndrome (PMS)